Making the Best Years of Our Lives: The Hollywood Classic that Inspired a Nation: ALISON MACOR, 2022, Austin, TX, University of Texas Press, pp. 240, $45.00 (hardcover). - Lozoya, Livia (Historical Journal of Film, Radio & Television, 2023)
Alison Macor's book, "Making the Best Years of Our Lives: The Hollywood Classic That Inspired a Nation," provides detailed context and explanations of how various world events influenced the creation of the film "The Best Years of Our Lives." Macor covers a wide range of topics, giving readers insight into the inner workings of the Hollywood studio system before, during, and after World War II. The book explores the film's realistic portrayal of post-traumatic stress disorder, disability, and rehabilitation, and highlights its importance and relevance for today's audiences. Macor's extensive research and use of primary source materials contribute to the scholarship on the film. Overall, the book is an informative and enjoyable read that advocates for the film's enduring legacy and showcases the resilience of the human spirit.